KARAKTERISTIK BENTUK ORNAMEN PADA BANGUNAN BERSEJARAH ISTANA KADARIAH PONTIANAK DAN KERATON ALWAZIKHOEBILLAH SAMBAS DI KALIMANTAN BARAT - Zain, Zairin; Khaliesh, Hamdil; Vica, Michael (architecture department, Engineering faculty, Universitas Diponegoro, 2024)
The ornaments in traditional Malay buildings are artistic manifestations of local traditions and customs. Ornaments on historic buildings in West Kalimantan have characteristic shapes designed to emphasize the structure, including the design of ornaments for palaces. Every element in architectural design embodies form in conceptual elements of points, lines, planes, and volumes formed into visual elements. The study was conducted in Exploratory and descriptive methods to the ornaments of historic buildings on the North coast of West Kalimantan, namely the Kadariah Palace in Pontianak and the Alwatzikhoebillah Palace in Sambas District. The study identifies characteristics of ornamental forms by examining the conceptual design elements of two historic buildings in West Kalimantan. Observations were made on the ornamental elements found in both buildings, which were found in the openings, roof edges, facade sections, and space division. This study concluded that the basic plane shapes of a rectangle, rectangle, triangle, and circle are used for ornamental forms of Kadariah Palace and Alwazikhoebillah Palace. Furthermore, the decorative design patterns in the Kadariah Palace and the Alwazikhoebillah Palace are formed by a combination of planes arranged by placing elements vertically, horizontally, diagonally, centrally, inclined, linearly, and at intersections. The shape character refers to a consistent way of designing regular shapes and patterns that provide ease of placement and connections